Calcium-permeable ion channels involved in glutamate receptor-independent ischemic brain injury - Li, Ming-hua (Nature Publishing Group, 2011)
Brain ischemia is a leading cause of death and long-term disabilities worldwide. Unfortunately, current treatment is limited to thrombolysis, which has limited success and a potential side effect of intracerebral hemorrhage. Searching for new cell injury mechanisms and therapeutic interventions has become a major challenge in the field. It has been recognized for many years that intracellular Ca(2+) overload in neurons is essential for neuronal injury associated with brain ischemia. However, the exact pathway(s) underlying the toxic Ca(2+) loading remained elusive. This review discusses the role of two Ca(2+)-permeable cation channels, TRPM7 and acid-sensing channels, in glutamate-independent Ca(2+) toxicity associated with brain ischemia.